OCCUPATIONAL HEALTH AND SAFETY AGENCY (UKK POST) HEALTH PROMOTION ON CLEAN AND HEALTHY LIVING AT WORK (PHBS) (CASE STUDIES ON INFORMAL WOOD FURNITURE WORKERS AT UKK POST, KENDIT HEALTH CENTER WORKSPACE, SITUBONDO REGENCY) - Isa Ma’rufi; Wiwien Sugih Utami; Sugeng Winarso; Nanik Kurniati (UPT Penerbitan Universitas Jember, 2022)
The OHE Post is a Community Based Health Effort (CBHE) for informal workers from, by and for workers by prioritizing promotive and preventive efforts. Workers in the informal sector have the potential for complex risks in their activities, which bring about various health problems for workers, one of which is low Clean and Healthy Living Behavior (CHLB).. The location of community service is at OHE Akar Dewa Jati Post and Putri Emas Post in Kendit District, Situbondo Regency, totaling 40 people. The method of implementation is to provide counseling related to hand washing using soap, healthy latrines, waste supply, use of clean water and Personal Protective Equipment (PPE), Focus Group Discussion and assistance from the Informal and Agricultural Sector Public Health Research Group (KESMASEK) at the University of Jember. The mentoring was carried out for one month, the results of the health promotion assessment were analyzed using the Wilcoxon signed rank test. The results and impact of this community service activity on CHLB is that there are differences in CHLB in the workplace for informal wood furniture workers in the working area of ​​the Kendit Health Center before and after health promotion. This includes improving the knowledge, attitudes and actions of the OHE Post furniture workers in the Kendit Health Center Work Area, Situbondo Regency. Keyword: OHE Post, CHLB, Kendit District, Situbondo Regency